Initial Reports of the Deep Sea Drilling Project 1976
DOI: 10.2973/dsdp.proc.33.133.1976
|View full text |Cite
|
Sign up to set email alerts
|

Marcasite in Miocene Calcareous Sediments from Hole 315A

Abstract: This chapter notes the occurrence of the pyrite dimorph, marcasite, as a minor diagenetic cement in light purple to bluish-white Miocene calcareous oozes. It occurs as the only mineral phase cementing small, elongate, gray aggregates with the morphology of worm burrows and may represent a worm's last stand. Scanning electron micrographs reveal clumps of typically fluted or curved orthorhombic dipyramids of marcasite supporting a framework of broken and corroded siliceous fossil fragments. Pyrite co-occurs in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1981
1981
1983
1983

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…That marcasite is missing from Site 505 sediments suggests that the upper limit of the pH range for marcasite formation-which seems to be at pH 7.0 or 7.1 (according to the measurements at Site 504)-is not reached yet at this site. Kelts (1976) found similarly low pH values in conjunction with marcasite occurrences in Miocene foraminifer nannofossil oozes from DSDP Site 315 (Leg 33, Fanning Island Fan, Line Islands). He discusses a drop in pH from above 7.0 to 6.0 initiated by sulfate-reducing bacterial activity which produces CO 2 and H 2 S, leading further to calcite dissolution and thence to physicochemical conditions within the microenvironment of organic processes which favor the direct formation of marcasite.…”
Section: Pyrite and Marcasitementioning
confidence: 75%
See 1 more Smart Citation
“…That marcasite is missing from Site 505 sediments suggests that the upper limit of the pH range for marcasite formation-which seems to be at pH 7.0 or 7.1 (according to the measurements at Site 504)-is not reached yet at this site. Kelts (1976) found similarly low pH values in conjunction with marcasite occurrences in Miocene foraminifer nannofossil oozes from DSDP Site 315 (Leg 33, Fanning Island Fan, Line Islands). He discusses a drop in pH from above 7.0 to 6.0 initiated by sulfate-reducing bacterial activity which produces CO 2 and H 2 S, leading further to calcite dissolution and thence to physicochemical conditions within the microenvironment of organic processes which favor the direct formation of marcasite.…”
Section: Pyrite and Marcasitementioning
confidence: 75%
“…Marcasite has not commonly been reported from sediments of the open marine environment. It is often said to form under slightly more-acid conditions than pyrite (Edwards and Baker, 1951;Betechtin, 1957;Tröger, 1967;Rickard, 1969;Kelts, 1976). Although this has been called in question by recent experimental work (Krauskopf, 1979), comparison between the pH values measured on interstitial-water samples obtained from sediments of Sites 504 and 505 (Mottl, Lawrence, et al, this volume) suggests that marcasite indeed forms under more-acid conditions than pyrite generally does.…”
Section: Pyrite and Marcasitementioning
confidence: 99%
“…We have noted similar patchy silicification, but it occurs only in impure chalks, which implies that clays may have partly inhibited silicification. Kelts (1976) briefly described burrows in cherts from the central Pacific (DSDP Leg 33); he found that burrows can act as conduits for silicification and can also inhibit silicification, which results in relict chalk patches in the chert. We agree with his observation.…”
Section: Discussionmentioning
confidence: 99%
“…Opal-CT lepispheres were replaced by quartz in one vein, and opal-CT may have been precursor to other vein quartz in Leg 62 samples. Many of these features have been described previously (Lancelot, 1973;Keene, 1976;Kelts, 1976). We studied four rock types that are uncommon or texturally odd.…”
Section: Thin-section and Sem Petrographymentioning
confidence: 92%
“…Iron sulfide minerals are common constituents of ancient marine sedimentary rocks (Edwards and Baker, 1951;Curtis, 1967;Love and Amstutz, 1966) as well as modern marine sediments (Love, 1967;Berner, 1970;Hein and Griggs, 1972;Sweeney and Kaplan, 1973). Sediments cored by DSDP generally contain small amounts of disseminated pyrite and marcasite, but only a few examples of concentrated occurrences of these minerals have been described (Kelts, 1976;Siesser, 1978).…”
Section: Introductionmentioning
confidence: 99%